Two‐Phase Flow Morphology and Phase Fractions in Larger Feed Line Sections. Issue 7 (6th May 2021) - Döß, Alexander; Schubert, Markus; Hampel, Uwe; Mehringer, Christian; Geipel, Christian; Schleicher, Eckhard
Abstract: The design of industrial feed line sections and the selection of appropriate inlet devices requires knowledge about the two‐phase flow morphology and phase fractions in order to reduce costly overdesign. Since experimental data for two‐phase pipe flows at industrial scale are hardly available, current prediction methods are subject to high unertainities. In this study, horizontal two‐phase flow morphologies for different industrial feed line sections were studied using wire‐mesh sensors at multiple locations along the pipe. The obtained phase fraction data are compared with correlations. Abstract : Commercial design of two‐phase feeds is subject to high uncertainties due to the lack of experimental flow morphology data. Industrial‐scale feed line sections were studied using wire‐mesh sensors. The evolving flow morphologies and the obtained phase fraction data are compared against available prediction methods.